This house is mine - Hansen, Dörte, 1964- (St. Martin's Press, 2016)
Vera is surprised when her niece shows up at her East Prussia farmhouse with her young son after fleeing a bad relationship in Hamburg and the pair find they have more in common than they ever thought possible.